2012
DOI: 10.3346/jkms.2012.27.10.1177
|View full text |Cite
|
Sign up to set email alerts
|

Early Start of Dialysis Has No Survival Benefit in End-Stage Renal Disease Patients

Abstract: The timing for dialysis initiationis still debated. The aim of this study was to compare mortality rates, using a propensity-score approach, in dialysis patients with early or late starts. From January 2000 to June 2009, incident adult patients (n = 836) starting dialysis for end-stage renal disease (ESRD) were enrolled. The patients were assigned to either an early- or late-start group depending on the initiation time of the dialysis. After propensity-score-basedmatching, 450 patients remained. At the initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…In this study, eGFR was used as an indicator to determine the initiation of dialysis. Twenty‐one studies estimated the GFR using a variant (4‐, 5‐, or 6‐variable) of the MDRD study equation , two studies estimated GFR using the Cockcroft‐Gault equation , and one study used the EPI equation . Two studies calculated GFR using the average of creatinine and urea clearance derived from a 24‐h urine collection .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, eGFR was used as an indicator to determine the initiation of dialysis. Twenty‐one studies estimated the GFR using a variant (4‐, 5‐, or 6‐variable) of the MDRD study equation , two studies estimated GFR using the Cockcroft‐Gault equation , and one study used the EPI equation . Two studies calculated GFR using the average of creatinine and urea clearance derived from a 24‐h urine collection .…”
Section: Resultsmentioning
confidence: 99%
“…While both the CCI and ESRD-CI are frequently used for risk adjustment in studies of dialysis patients [17][18][19][20][21][22], only a few studies have attempted to validate either index [15,23,24]. In addition, these validation studies have limitations including incomplete inclusion of all necessary comorbid conditions, and validation techniques that are not specific to time-to-event analyses [15,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several similar reports have indicated that decreased serum creatinine levels are associated with increased mortality after AKI (Bagshaw et al 2009(Bagshaw et al , 2012Ostermann and Chang 2009;Jamale et al 2013). Interestingly, several studies have recently reported that in patients with advanced chronic kidney disease, the early initiation of RRT based on eGFR was unable to improve patient survival (Cooper et al 2010;Chang et al 2012), and even led to worse survival and clinical outcomes (Crews et al 2014). Considering these findings, clinicians should not initiate RRT based solely on serum creatinine levels and eGFR.…”
Section: Discussionmentioning
confidence: 99%